Psychological Features of Police Officers’ Conflict Behavior: Gender Aspect (Law and Safety, 2021)
To date, there are no scientifically sound recommendations for resolving conflicts in law enforcement activity, there are no methods for resolving conflicts, and there are no means for managing the conflict behavior of police officers taking into account the gender aspect.The purpose of the work is to conduct a comprehensive study of psychological characteristics of conflict behavior of police officers taking into account the gender aspect. Theoretical and empirical methods were used in the work. According to the results of conducted theoretical analysis the author has noted the psychological and moral preconditions for conflict prevention with the participation of police officers taking into account the gender aspect.According to the method of “Personal Aggression and Conflict” the highest rates in the first group (police officers – women) were obtained on the scale of “conflict”. The lowest rates among women are on the scale of “negative aggression”. The highest rates in the second group (police officers – men) – were on the scales of “conflict” and “positive aggression”. The lowest rates were on the “negative aggression” scale.The highest rate on the scale of “adaptation” according to the method of “Diagnosis of Style of Behavior in Conflicts” (K. Thomas) is both among women and men. Women and men according to the “rivalry” scale have a low rate.The highest rate for women according to the method of “Diagnosis of Conflict Resolution Strategies" was on the “adaptation” scale. The highest rate among men was the scale of “cooperation”. Prevention rates among women are low. Men have the lowest rate on the “competition” scale.Analyzing the results of the study of the style of behavior of police officers in conflict situations within the gender aspect, it was found out that the higher the tendency to avoid conflict, the less are manifestations of styles of rivalry, cooperation and adaptation. At the same time, as the length of service increases, the tendency to adaptive style of behavior in conflict situations increases, which may be associated with manifestations of professional deformation and burnout; strategies of compromise and avoidance in conflict situations are in the lead.
Keywords: gender; law enforcement system; gender aspect; conflict behavior; styles of behavior in a conflict; a conflict.